Application of the Recitation Method to improve Analytical Thinking Ability and Learning Outcomes - Maria Marlin Sutejo; Dwi Noviani Sulisawati (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2021)
The recitation method is a learning method that is characterized by the work of assignments by students. Analogy ability is the ability of a person (student) in solving problems by drawing conclusions based on the similarity of the process or the data provided. Learning outcomes are abilities possessed by students after students carry out learning activities. This study aims to describe how the process of applying the Recitation method improves students' analogical thinking skills and student learning outcomes. The subjects in this study were students of class VIIIA SMP Satya Dharma Jalan Puger, Balung District, Jember Regency. Data collection techniques were carried out with observation sheets, tests, and documentation. This research uses classroom action research (CAR). The results of the study can be seen from the acquisition of the percentage of teacher and student activities in the first cycle of 94.87% and 87.17% respectively, while in the second cycle the percentage of teacher and student activities is the same, namely 97.43%. Analogy thinking ability and student learning outcomes in the first cycle respectively get an average of 41.26% and 60% while in the second cycle the average Analogy thinking ability and student learning outcomes are 66.98% and 80.47%. So it can be concluded that applying the recitation method can improve students' analytical thinking skills and student learning outcomes.